A giant hybrid organic–inorganic octahedron from a narrow rim carboxylate calixarene. Issue 95 (13th November 2020) - Machado dos Santos, Fernando; Edivirges Alvarenga, Meiry; Valdo, Ana Karoline Silva Mendanha; Rabelo, Renato; Cangussu de Castro Gomes, Danielle; de Fátima, Ângelo; Vinicius Costa Lara, Thiago; da Silva, Cleiton Moreira; Tasso, Thiago Teixeira; Neto, João Honorato Araujo; Batista, Alzir Azevedo; Ayala, Alejandro Pedro; et al.
Abstract : Here we discovered an unprecedented giant octahedral coordination compound bearing 16 Zn 2+, 12 Na +, 8 O 2−, 4 OH −, 13 H2 O and 6 L 4− ligands [L 4− = fully deprotonated tetra(carboxymethoxy)calix[4]arene]. Abstract : Here we discovered an unprecedented giant octahedral coordination compound bearing 16 Zn 2+, 12 Na +, 8 O 2−, 4 OH −, 13 H2 O and 6 L 4− ligands [L 4− = fully deprotonated tetra(carboxymethoxy)calix[4]arene]. Its structure was elucidated by single-crystal X-ray diffraction, wavelength-dispersive X-ray spectroscopy and MALDI-TOF mass spectrometry. This compound, Zn8 Na6 L6 ⊃Zn8 Na6 O8 (OH)4 (H2 O)13 (external⊃internal), has eight tetrahedral zinc ions forming the coordination vertices of an outermost cube where carboxylate groups from the sodium calixarenes are anchored. Its core consists of eight Zn 2+, six Na +, eight O 2−, and four OH − distributed over three layers, besides thirteen coordinated H2 O molecules.